1977
DOI: 10.1002/eji.1830070402
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific genetic regulation of antibody responsiveness in the mouse

Abstract: Four lines of mice were produced by selective breeding for quantitative agglutinin responsiveness to flagellar (f) or somatic (s) antigens (Ags) of Salmonellae: high (H) or low (L) responder lines to fAg and H and L responder lines to sAg. The Salmonellae contained both f and sAgs, the Ag used to perform the selection was the Selection Ag and the other was the Associated Ag. The selective breeding produced a progressive interline separation with an equivalent effect for both Ags. After 15 generations (F15) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Highly infested hosts receive large amounts of tick saliva, which contains many immunosupressants, including immunoglobulin-binding proteins, which are abundantly transcribed in salivary glands of the feeding male tick [32], coinciding with the appearance of the host’s acquired immune response. The genetic composition of hosts affects the nature of the antibody response, including levels of total immunoglobulins [3337], the IgG subclasses recruited, and antibody specificities [33, 38]. On the other hand, ticks ingest large amounts of host immunoglobulins presenting antibody activity [39].…”
Section: Resultsmentioning
confidence: 99%
“…Highly infested hosts receive large amounts of tick saliva, which contains many immunosupressants, including immunoglobulin-binding proteins, which are abundantly transcribed in salivary glands of the feeding male tick [32], coinciding with the appearance of the host’s acquired immune response. The genetic composition of hosts affects the nature of the antibody response, including levels of total immunoglobulins [3337], the IgG subclasses recruited, and antibody specificities [33, 38]. On the other hand, ticks ingest large amounts of host immunoglobulins presenting antibody activity [39].…”
Section: Resultsmentioning
confidence: 99%
“…In selections III and IV, based on responsiveness to S.tm. Ag [20], no modification of macrophage catabolic activity towards Ag could be found [12,13]. LII I and L w mice, though, were found more resistant than their H mice counterparts to S. tin.…”
Section: -8534/89/$0350 © 1989 Federation Of European Microbiolomentioning
confidence: 99%
“…H and L mice were from selections I, II and IV A, based on Ab responsiveness to heterologous erythrocytes [10,21] and from selections III and IV, based on Ab responses to S.tm. Ag [20]. Mice of both sexes were used at 2-4 months.…”
Section: Micementioning
confidence: 99%
“…This bidirectional selective pressure resulted in the accumulation of alleles at multiple quantitative trait loci (QTLs) in each H and L line endowed with opposite modulatory effects on the various steps of antibody biosynthesis [27]. The differences in antibody responses between H III and L III lines are not restricted just to the selection immunogen but encompass a wide range of complex antigens, showing evidence for multispecific effects of the relevant genes [28, 29]. Genetic analyses indicated that 5–10 QTLs regulate the antibody production phenotype, and a QTL mapping experiment using microsatellite markers yielded three highly significant QTLs on chromosomes 3, 8, and 9 [30].…”
Section: Introductionmentioning
confidence: 99%